(3EHQGe GdJYGbO GdEdcJQhfi h EKHGJg (B/ s - (3EjeGf YHO GdLhGO eUWai EHQGgjes; (3SYjO SdjeGf LHQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2016)
(3JMOK GdHGMK Yf edGeM GdJYGbO GdEdcJQhfi(B: (3h Yf fXe GdJYGbO ai GdYUhQ GdeNJdaI(B: (3h eGgjI GdJYGbO GdEdcJQhfi(B: (3h JejjR GdJYGbO GdEdcJQhfi Yf ZjQg ef GdYbhO ef MjK WQjbI GdJYGbO(B: (3h YbhO GdHjFI GdEdcJQhfjI(B. (3h eQGMd EHQGe GdJYGbO GdEdcJQhfi(B: (3eQMdI GdJaGhV Ydi GdYbO GdEdcJQhi(B: (3h eGgjI GdJaGhV GdEdcJQhfi(B: (3eagheg h CgejJg ai eHMK Chd(B: (3Ke NUGFUg ai eHMK KGf(B: (3h JejjR GdJaGhV GdEdcJQhfi YeG bO jTJHg Hg aj eHMK KGdK(B. (3GdJRGeGJ GdCWQGa ai eQMdI GdJaGhV GdEdcJQhfi GdeHMK GdChd GdGdJRGeGJ GdCSGSjI ai eQMdI GdJaGhV GdEdcJQhfi(B: (3h GdeHMK GdKGfi GdGdJRGeGJ GdJGHYI ai eQMdI GdJaGhV GdEdcJQhfi(B. (3h LRGA GdENdGd HGdGdJRGeGJ GdfGTFI ai eQMdI GdJaGhV(B: (3GdeHMK GdChd ddGJaGbGJ GdJi JJNdd eQMdI GdJaGhV h UhQ GdNWC ai GdJaGhV(B. (3h GdeHMK GdKGfi dWHjYI GdeSFhdjI ai eQMdI GdJaGhV, CeG GdeHMK GdKGdK GdJYhjV Yf GdVQQ ai eQMdI GdJaGhV(B. (3h eQMdI GdJYGbO GdEdcJQhfi(B: (3hLhO GdJQGVj JfGhdfG ajg GdJYHjQ Yf GdEQGOI aji GdJYGbO GdEdcJQhfi(B: (3h GdEjLGH GdEdcJQhfi(B: (3h GdbHhd GdEdcJQhfi(B: (3aj KdGKI eHGMK eJJGdjI(B. (3h UMI GdJQGVj aj GdJYGbO GdEdcJQhfi(B: (3h GdCgdjI ai GdJYGbO GdEdcJQhfi(B: (3h GdeHMK GdKGfi Ndh GdEQGOI ef GdYjhH(B. (3h EKHGJ GdJYGbO GdEdcJQhfi LGA ai GdcJGHI GdEdcJQhfjI h eGgjI GdcJGHI GdEdcJQhfjI(B: (3h TQhW GdcJGHI GdEdcJQhfjI h GdMLjI GdbGfhfjI ddcJGHI GdEdcJQhfjI ai GdEKHGJs
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdeOfj (B2016.s
(3HHdjhLQGajG(B: (3UaMGJ (B455-494.s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdEKHGJ GdGdcJQhfis; (3GdJhbjY GdGdcJQhfjs; (3GdJaGhV GdGdcJQhfjs; (3GdJYGbO GdGdcJQhfj s; (3YbhO GdHjFI GdEdcJQhfjIs; (3fXe GdJYGbO GdEdcJQhfis; (3GdJOdjS h GdGSJZdGd s; (3MLjI GdcJGHI GdGdcJQhfjIs; (3GdeMQQ GdGdcJQhfjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdeOfjs